2021
DOI: 10.1007/s13300-021-01169-w
|View full text |Cite
|
Sign up to set email alerts
|

Renal Complications and Duration of Diabetes: An International Comparison in Persons with Type 1 Diabetes

Abstract: Introduction: Renal complications are both a marker of previous suboptimal glycaemic control and a major risk factor for cardiovascular disease in persons with type 1 diabetes (T1D). The aim of the study was to evaluate the prevalence of renal complications in persons with T1D in four geographical regions. Methods: Nationwide registry data from Austria/Germany, Sweden and the US were used to estimate the prevalence of renal complications from January 2016 until September 2018.Chronic kidney disease (CKD) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In a recent study including patients from four countries, renal complications were still common in patients with diabetes onset over the last 20 years, and the majority of patients had glucose levels above target. 36 Hence, improved prevention in people with T1D and cardiorenal complications should be the focus of attention in clinical practice and research to reduce the gap in mortality over time.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study including patients from four countries, renal complications were still common in patients with diabetes onset over the last 20 years, and the majority of patients had glucose levels above target. 36 Hence, improved prevention in people with T1D and cardiorenal complications should be the focus of attention in clinical practice and research to reduce the gap in mortality over time.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 20%-40% of people with diabetes will develop diabetic kidney disease, and it is the leading cause of end-stage renal failure[ 5 , 6 ]. A recent study showed that up to 5.1% of people with type 1 diabetes in Germany and Austria had an estimated glomerular filtration rate (eGFR) below 30 mL/min, and for Sweden and United States, the corresponding figures were 1.5% and 2.1%[ 7 ]. Advanced CKD increases the risk of hypoglycemia and great glycemic variation, and therefore it can be helpful to monitor blood glucose with a CGM or isCGM[ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%